Physicochemical Characteristics and Irrigation Quality of Water in Faya and Surrounding Areas Plateau State, Nigeria (Journal of Pure and Applied Sciences (Science Forum), 2025)
This study evaluates the physicochemical properties and irrigation suitability of various water sources in Faya and its surrounding environs within Plateau State, Nigeria. A total of 25 water samples were systematically collected during the dry season from both surface water bodies (including rivers, streams, ponds, dams, and mining ponds) and groundwater sources (wells and boreholes). These samples were analyzed for key physical parameters—pH, electrical conductivity (EC), total dissolved solids (TDS), turbidity, salinity, and total hardness—as well as major chemical constituents such as calcium (Ca²⁺), magnesium (Mg²⁺), sodium (Na⁺), chloride (Cl⁻), sulfate (SO₄²⁻), bicarbonate (HCO₃⁻), nitrate (NO₃⁻), nitrite (NO₂⁻), phosphate (PO₄³⁻), and fluoride (F⁻). In addition, irrigation water quality indices were computed, including the Sodium Adsorption Ratio (SAR), Magnesium Adsorption Ratio (MAR), and Kelley’s Ratio (KR). The results show that most water samples had pH values within the acceptable limits prescribed by the World Health Organization (WHO). However, elevated levels of TDS, turbidity, and hardness were observed in several samples. Notably, both groundwater and surface water sources exhibited fluoride and nitrate concentrations exceeding WHO guidelines, indicating potential health risks, particularly for long-term consumption. While SAR values remained below 10 in most cases—suggesting a low sodium hazard to soil permeability—MAR values exceeded 50% in the majority of samples, pointing to a significant magnesium dominance. Furthermore, elevated KR values in select locations suggest a risk of sodium-induced degradation of soil structure. These findings underscore the combined effects of geogenic processes (such as mineral weathering) and anthropogenic activities (including agricultural runoff and artisanal mining) on water quality. The study highlights the critical need for regular monitoring, effective water treatment strategies, and integrated water resource management to ensure the suitability of water for both irrigation and human use in the region.